Agroforestry-Silvopastoral Systems Suitability for the Plateau Landforms: Devrekani Plateau (Northern Turkiye) - Duran, Celalettin (Geoplanning: Journal of Geomatics and Planning, 2024)
The Devrekani Plateau, located in the Kure Mountains massif (Kastamonu-Türkiye), is a geomorphological unit with flat areas ranging between 1000 and 1300 meters in altitude. Agriculture, animal husbandry, and forestry activities are standard on the plateau. Due to environmental constraints, versatile, holistic, and sustainable land use plans are needed in such high areas. This study examines land use patterns compatible with natural environmental conditions for the Plateau Landforms. Agroforestry-silvopastoral systems where agriculture, pasture, forest lands, and recreational functions are applied together have been evaluated in the study area. Criteria that have a high relationship with land use have been identified. Using Geographic Information Systems, weighted overlay analysis was carried out with factor maps regarding Lithology, Slope, Elevation, and Actual Land Use. The model output reveals that the regions between agriculture and forest are the most suitable for the agroforestry-silvopastoral systems (outside urban areas) and recreation. The most suitable areas for mixed land use plans on the plateau are generally karst areas with sparse vegetation, located above 1200 meters, and having a 6-12% slope. The lower border of these areas is agricultural areas with flat or nearly flat slopes, commonly formed by alluviums. The upper limit consists of forest areas with steep slopes surrounded by high hills. Implementing agroforestry-silvopastoral land use models on plateau landforms can be an effective strategy for sustainable environmental management and land use.